Disruption of the brain–esophagus axis in obese patients with heartburn - Ribeiro, Marcelo; Forcelini, Cassiano Mateus; Navarini, Daniel; Soder, Ricardo Bernardi; Fornari, Fernando (Diseases of the esophagus, 2022)
Obesity is a risk factor for gastroesophageal reflux disease. Studies addressing the brain–esophagus axis in obese are lacking. In obese with and without heartburn, we assessed: (i) the brain responses to esophageal acid perfusion during functional brain imaging; (ii) esophageal impedance baseline before and after acid perfusion; and (iii) abdominal fat distribution. In this exploratory study, 26 obese underwent functional magnetic resonance imaging (fMRI) of the brain combined with esophageal acid perfusion. Esophageal impedance baseline was determined before and after fMRI, followed by tomographic quantification of the abdominal fat. Among 26 obese (54% men, 39.7 years old, 33.5 kg/m2), there were 17 with heartburn and 9 without heartburn. Before fMRI, the esophageal impedance baseline was lower in obese with heartburn than without heartburn (median 1187 vs. 1890 Ω; P = 0.025). After acid perfusion, impedance baseline decreased in obese with heartburn (from 1187 to 899 Ω; P = 0.011) and was lower in this group than in obese without heartburn (899 vs. 1614 Ω; P = 0.001). fMRI task-residual analysis showed that obese with heartburn presented higher functional connectivity in several brain regions than obese without heartburn. Abdominal fat area did not differ between obese with and without heartburn either for total (72.8 ± 4.4% vs. 70.3 ± 6.0%; P = 0.280), subcutaneous (42.2 ± 9.0% vs. 37.4 ± 9.0%; P = 0.226), or visceral (30.6 ± 7.9% vs. 33.0 ± 7.8%; P = 0.484). In subjects with obesity, the brain–esophagus axis is disrupted centrally with higher functional brain connectivity and peripherally with decreased esophageal mucosa integrity in the presence of heartburn.